Acceptable durability of split inner table graft for the reconstruction of a bone defect in pterional craniotomies: a case series - Kweon, Gi-Young; Park, Jaechan; Son, Wonsoo (Frontiers in Surgery, 2023)
Objective : In a pterional craniotomy, the bone defect was reconstructed by a surgical technique using an autogenous bone graft instead of commercially available alloplastic materials. The technical feasibility, durability of the grafted bone, and cosmetic outcomes were all evaluated.Methods : After a pterional craniotomy, the bone defect at the frontobasal burrhole and drilled sphenoid wing was reconstructed using an autogenous split inner table graft (1 x 2 cm) harvested from the craniotomy bone flap.The bony reconstruction technique was performed successfully on 9 patients with intracranial aneurysms. Twelve to nineteen months after the surgery, a volumetry study using three-dimensional skull images reconstructed from computed tomography angiography (CTA) showed that the area decrease of the split inner table graft due to bone resorption was minimal, ranging from 5.7% to 14.8% in 6 patients. In the other 3 patients, the bone resorption was more substantial, ranging from 21.2% to 27.5%. However, in the latter 3 cases, the resorption was mainly limited to the posterior part of the split inner table graft that was covered by the temporalis muscle and did not affect the cosmetic outcomes. The resultant cosmetic outcomes for the 9 patients were all favorable with only a slight or no anterior temporal hollow.The proposed surgical technique using a split inner table graft harvested from the craniotomy bone flap would seem to be an available option for reconstructing the bone defect at the frontobasal burrhole and drilled sphenoid wing after a pterional craniotomy.